Oxidative stress-mediated apoptosis via the SLC23A2-ascorbic acid interaction contributes to cleft lip development - Yin, Bin; Xu, Yi Chen; Lu, Yong (Frontiers in Pediatrics, 2025)
ObjectivesNon-syndromic cleft lip only (NSCLO) is a common subtype of cleft lip with/without cleft palate (CL/P). Previously, we found that SLC23A2 is closely related to the occurrence of cleft palate through gene–environment interaction studies, but whether SLC23A2 is related to the occurrence of cleft lip has not been reported.DesignFirst, the genotyping data of single-nucleotide polymorphisms (SNPs) at SLC23A2 in 1,047 patients with NSCLO and 2,255 normal controls were extracted from two previous genome-wide association studies (GWASs) for an association analysis. Then, the interaction effect of SLC23A2, reactive oxygen species (ROS), and ascorbic acid (AA) on oxidative stress and apoptosis levels in the human oral epithelial-derived cell line (GMSM-K) and zebrafish was verified in vitro and in vivo. Finally, the mechanism of how SLC23A2 is involved in the occurrence of cleft lip was initially explored using RNA sequencing.ResultsThe association analysis showed that 10 SNPs located at SLC23A2 were significantly correlated with NSCLO. In vitro experiments have shown that knockdown of SLC23A2 in GMSM-K inhibits the expression of COL9A3 in the PI3K-Akt signaling pathway, promoting an increase in ROS and triggering increased apoptosis. The interaction results showed that the ROS and apoptosis levels increased in GMSM-K cells with normal SLC23A2 gene function when stimulated by Sin-1 (exogenous ROS mimics) and ROS and apoptosis levels can be reduced by AA supplementation. GMSM-K cells became more sensitive to Sin-1, and AA supplementation was ineffective after SLC23A2 knockdown. In addition, increased ROS and apoptosis levels were also observed in slc23a2-MO zebrafish, and could not be rescued by AA supplementation.ConclusionSLC23A2 was significantly associated with NSCLO. The SLC23A2/exogenous ROS/AA interaction is involved in lip and craniofacial development by influencing the levels of ROS and apoptosis.